2016
DOI: 10.1155/2016/1574971
|View full text |Cite
|
Sign up to set email alerts
|

Bothrops jararaca and Bothrops erythromelas Snake Venoms Promote Cell Cycle Arrest and Induce Apoptosis via the Mitochondrial Depolarization of Cervical Cancer Cells

Abstract: Bothrops jararaca (BJ) and Bothrops erythromelas (BE) are viper snakes found in South-Southeast and Northeast regions of Brazil, respectively. Snake venoms are bioactive neurotoxic substances synthesized and stored by venom glands, with different physiological and pharmacological effects, recently suggesting a possible preference for targets in cancer cells; however, mechanisms of snakes have been little studied. Here, we investigated the mechanism responsible for snake crude venoms toxicity in cultured cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Results showed that crude snake venom induces depolarization of the mitochondrial membrane in a dose-dependent manner ( Figure 3A). This result was very interesting since the evaluations were performed using sub-lethal doses and acute treatment time, indicating that accumulated mitochondrial damage could be the cause of cell death, mainly intrinsic apoptosis pathway, as evidenced by another research [23].…”
Section: Crude Snake Venom Induces Mitochondrial Damagementioning
confidence: 78%
See 1 more Smart Citation
“…Results showed that crude snake venom induces depolarization of the mitochondrial membrane in a dose-dependent manner ( Figure 3A). This result was very interesting since the evaluations were performed using sub-lethal doses and acute treatment time, indicating that accumulated mitochondrial damage could be the cause of cell death, mainly intrinsic apoptosis pathway, as evidenced by another research [23].…”
Section: Crude Snake Venom Induces Mitochondrial Damagementioning
confidence: 78%
“…Nevertheless, this outcome was not observed in the crude venom from B. jararaca, neither in 24h nor in 48h of treatment ( Figure 2). Recently it was described that crude venom from B. jararaca and B. erythromelas exhibited a cytotoxic effect promoting cell cycle arrest and inducing apoptosis through mitochondrial depolarization in cervical cancer cells [23]. Mitochondrial damage is related to intrinsic apoptosis pathway activation by cytochrome c release and caspase cascade, mediated production of hydrogen peroxide [13].…”
Section: Oxidant Potential Of Crude Venom In Vitromentioning
confidence: 99%
“…Whether venom compounds affect the cell cycle is also possible. For example, it was reported that snake venom (Bernardes-Oliveira et al, 2016), and more precisely Phospholipases A2 (Prinholato da Silva et al, 2015), can lead to cell cycle arrest at the G0/G1 phase. M. bornumelleri's venom is known to contain Phospholipases A2 (Accary et al, 2015); therefore, it will not be surprising if the venom affects the cell cycle in a similar way to what was reported previously (Bernardes-Oliveira et al, 2016;Prinholato da Silva et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…SiHa and HeLa cells were cultivated in a 96-well plate at an initial density of 5 × 10 3 cells/well and after 24 h were treated with 200 μ L/well of different concentrations of TsV venom (50, 125, 250, and 500 μ g/mL) and CDDP 33 μ g/mL [16] [Cisplatin, citoplax, 50 mg from Bergamo Taboão da Serra, SP, Brazil, drug control]. During the procedures we used as negative control (NC) cells with only culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, chemotherapy has been shown in some cases to have a limited effect on the cure and survival of patients, particularly in patients with cervical cancer, and especially when the disease is advanced; what is more it may promote chemoresistance or even relapse, which limits the success [1315]. Therefore, an urgent goal in medicine is the search for new biomarkers with lower cytotoxicity, with less side effects, and, at the same time, selective with normal cells, or at least presenting minimal effects [16, 17].…”
Section: Introductionmentioning
confidence: 99%